2024
DOI: 10.1039/d3py01215h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of triphenylamine-based nanoporous organic polymers for highly efficient capture of SO2 and CO2

Jun Yan,
Yan Tan,
Sihan Tong
et al.

Abstract: The fabrication of nanoporous organic polymers (NOPs) for the highly efficient capture of sulfur dioxide (SO2) and carbon dioxide (CO2) through the self-polymerization of an AB2 monomer presents significant challenges....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 51 publications
(101 reference statements)
0
0
0
Order By: Relevance
“…This finding underscores the critical role of substituent effects in modulating the adsorption properties of these materials. The SO 2 /CO 2 selectivity of NPAN-3 at 298 K and 100 kPa (87.7) was comparable to those of porous materials, as seen in Table S3, such as ANOPs (50.5−64.7), 11 DUTs (33− 37), 4 POPs (19.5−31.0), 44 TAM-POF (83), 45 HNIP-TBMBs (50−91), 36 XJ-COFs (39−118), 46 ELM-12 (30), 39 Fe-soc-MOF (32), 47 GU-1 (15.9, 296.2 K), 48 ECUT-11 (25.2, 1:99 (v/v) of SO 2 /CO 2 ), 49 and ECUT-Th-60 (27, 1:99 (v/v) of SO 2 /CO 2 ). 50 Adsorption of the Four NPANs for I 2 .…”
Section: ■ Results and Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This finding underscores the critical role of substituent effects in modulating the adsorption properties of these materials. The SO 2 /CO 2 selectivity of NPAN-3 at 298 K and 100 kPa (87.7) was comparable to those of porous materials, as seen in Table S3, such as ANOPs (50.5−64.7), 11 DUTs (33− 37), 4 POPs (19.5−31.0), 44 TAM-POF (83), 45 HNIP-TBMBs (50−91), 36 XJ-COFs (39−118), 46 ELM-12 (30), 39 Fe-soc-MOF (32), 47 GU-1 (15.9, 296.2 K), 48 ECUT-11 (25.2, 1:99 (v/v) of SO 2 /CO 2 ), 49 and ECUT-Th-60 (27, 1:99 (v/v) of SO 2 /CO 2 ). 50 Adsorption of the Four NPANs for I 2 .…”
Section: ■ Results and Discussionsupporting
confidence: 56%
“…Wang et al reported the synthesis of a highly stable three-dimensional viologen-based porous organic framework that exhibits high selectivity for SO 2 /CO 2 (467 at 298 K and 100 kPa). Yan et al synthesized a triphenylamine-based NOP with a Brunauer–Emmett–Teller (BET) specific surface area of 1016 m 2 /g and an SO 2 adsorption capacity of 21.9 mmol/g. All of the studies discussed above emphasize the significance of introducing nitrogen-containing functional groups into NOPs to provide the polymers with additional adsorption sites and enhance the adsorption capacities of the polymers for toxic gases and iodine. It is worth mentioning that NOPs are generally synthesized using expensive monomers and complex processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triphenylamine (TPA)-based POPs have a special appeal among POPs because of their potential to tolerate high levels of heat, which are frequently encountered in industrialized CO 2 capture operations. They also do not break down easily when other gasses are present [31][32][33][34][35][36][37]. Notably, TPA's steric and electronic properties are flexible enough to affect CO 2 capture effectiveness [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…14 The POP-Py exhibited a notable SO 2 capacity of 10.8 mmol g −1 , but an SO 2 /CO 2 selectivity of only 31.0. Our group synthesized two triphenylamine-based NOPs through the self-condensation of 4-(N,Ndiphenylamino)benzaldehyde and 4′-(diphenylamino)biphenyl-4-carbaldehyde, demonstrating an SO 2 adsorption amount of 10.9 mmol g −1 at 100 kPa and 298 K. 8 The NOPs described in the literature have demonstrated a high adsorption capacity for SO 2 , yet they exhibit limited selectivity toward CO 2 or N 2 . Therefore, the challenge remains in designing and preparing NOPs with both high SO 2 adsorption uptake and selectivity for practical applications.…”
Section: ■ Introductionmentioning
confidence: 99%